Politik Hukum Pemberhentian (Pemakzulan) Presiden dan/atau Wakil Presiden di Indonesia dalam Prespektif Negara Hukum dan Demokrasi - Akbar, Muhammad Aksan (Faculty of Law, Universitas Pattimura, 2020)
This study aims to determine the legal politics of dismissing the President and / or Vice President in Indonesia. The research method used normative research with a statute approach and a conceptual approach and analyzed descriptive qualitative. The results show that the dismissal of the President and / or Vice President in Indonesia is based on an understanding of a democratic state and an understanding of the rule of law . The application of the concept of a democratic state is carried out through a prior statement of opinion by the DPR and dismissal by the MPR. Meanwhile, the application of the rule of law is carried out through a legal process (forum previlegiatum), namely through examination of trials and decisions in the Constitutional Court. The choice of law is intended to strengthen the presidential system which adheres to the fixed term principle of the position of President and / or Vice President and to ensure the implementation of a stable state government.